Sustainable Economic Development through Downstream Frankincense (Styrax Benzoin) Production in an Effort to Increase Farmers' Income in North Sumatra - Ika Pratiwi Simbolon; Lilis Susilawaty; Ivana Valencia (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study analyzes the potential of a frankincense downstreaming program as a strategy to increase community income in North Sumatra, the world's largest frankincense-producing province. Data on frankincense production and exports from North Sumatra for the 2020-2024 period show significant dominance in the global market, yet the added value received by farmers remains relatively low. This paper identifies the obstacles faced by farmers, such as limited access to processing technology, price fluctuations, and a lack of downstream infrastructure. Through a review of data from the Statistics Indonesia (BPS), the Ministry of Trade, and the North Sumatra Plantation Office, as well as a literature review related to sustainable economic development programs, this study proposes a downstreaming solution that focuses on the diversification of frankincense derivative products, increasing farmer human resource capacity, and an active government role in creating a conducive industrial ecosystem.